PENERAPAN MODEL PEMBELAJARAN REACT UNTUK MEREMEDIASI MISKONSEPSI PESERTA DIDIK SMA PADA MATERI FLUIDA DINAMIS - Adzanianto, Bekti Purwo; Djudin, Tomo; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to determine the effectiveness of the application of the instructional model of relating, experiencing, applying, cooperating, transferring (REACT) in remediating students with misconceptions in dynamic fluid material in State Senior High School 1 Sungai Raya. This research uses pre-experimental design with the design of one group pretest-posttest. The samples were students of class XI IPA 3 with total of 27 students chosen by means of intact group. The data collection instrument uses a multiple choice diagnostic test with open reason. The results of the study show that the average percentage of students' misconception was 80.74% at the pre-test. There was a decrease in the number of students with misconceptions after remediation using the REACT learning model with an average percentage of 46.81%. Students' conceptions changed significantly ( = 29.03; df = 1; α = 5%) after being given remediation learning. The effectiveness of remediation is indicated by the value of decline in the number of students with misconceptions of each indicator with an average of 0.47, so according to the principle the phalanx effectiveness it is moderate (0.31 <ΔS <0.70). This research is expected to be used as an alternative to remedy students’ misconceptions, especially in physics. Keywords: Remediation, Misconception, REACT Model, Dynamic Fluids Material